A Comparative Study of the Psychoanalytical Portrayal of the Women Characters by Virginia Woolf and Zoya Pirzad - Fatemeh Sadat Basirizadeh; Mahnaz Soqandi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Looking backwards at a century of capricious discourses, now after another turn of the century, one easily comes to the common point in all Feministic discourses; which all are as efforts to prove women's presence and their equality to men in various aspects of life. The passage of the decades did not mutate the nature of all these feminine studies; just have posed the topic in diverse areas; for the whole body of the Feminist dialogisms and ideas were appointed by patriarchal discourses. This indicates that the current feminist dialogisms are not totally feminine discourses, rather, feminine-masculine ones formed out of men's mischievousness saving their patriarchal authority which changes the discourses to a masculine/feminine relation. However, what nowadays Feminism, as a school of thought, needs is a feminine intuition, that is a moment of feminine epiphany, by which not only women will be able to reach a new understanding of femininity but men also will recognize the essence/existence of females. Discussing Virginia Woolf’s dialogism in ‘A Room of One’s Own’ and two novels by Zoya Pirzad (Persian narratives of a highly male dominated society) the study concludes that Feminism needs an intuitive feminine epiphany; an epiphany that both sexes should come to in a society, to enable the school of feminism to come to a purely feminine dialogics and be released from all the mischievous feminine-masculine discourses.